Endo-β-1, 3-glucanase digestion combined with the HPAEC-PAD-MS/MS analysis reveals the structural differences between two laminarins with different bioactivities. (15th August 2018) - Liu, Zhonghua; Xiong, Yuanjing; Yi, Lin; Dai, Rujuan; Wang, Yanxin; Sun, Mingliang; Shao, Xiaoyan; Zhang, Zhenqing; Yuan, Sheng
Graphical abstract: Highlights: An accurate method for the determination of laminarin structure was established. Laminarin structure was analysed by using enzymatic digestion and HPAEC-PAD-MS/MS. The laminarin from Laminaria digitata contains 9.51% b-1, 6 glycosidic bonds only in the branches and the DB of it is 7.68%. The laminarin from Eisenia bicyclis contains 19.42% b-1, 6 glycosidic bonds in backbone, and more and longer β-1, 6 branches. The antioxidant and antimicrobial activity of those laminarins are different, because the structures of them are different. Abstract: To resolve the structure of laminarin, the recombinant endo-β-1, 3-glucanase from Coprinopsis cinerea, which has specific activity on β-1, 3 glycosidic bond and could hydrolyze the laminarin with complex structure, was used to hydrolyze laminarin. Then, the structures of enzyme-resistant oligosaccharides were quantitatively and qualitatively analysed by high-performance anion exchange chromatography coupled with mass spectrometry. The laminarin from Laminaria digitata contains 9.51% β-1, 6 glycosidic bonds only in the branches (branch degree 7.68%). The laminarin from Eisenia bicyclis contains more β-1, 6 glycosidic bonds: 19.42% β-1, 6 glycosidic bonds in backbone and more and longer β-1, 6 branches (branch degree 25.99%). The differences in the ratio of glycosidic bonds and branch degree influence their bioactivity: the antioxidant activity and the antimicrobial activity against Gram positive bacteria of the laminarin from E. bicyclis is stronger than the laminarin from L. digitata, but the antimicrobial activity on Gram negative bacteria of the laminarin from E. bicyclis is weaker.